Floral and pollination biology, breeding system and nectar traits of Callistemon citrinus (Myrtaceae) cultivated in India - Chauhan, S. (2017)
This study reports the influence of habitat on floral (flower and nectar characteristics, phenology) and pollination biology (flower visitors and breeding system) on Callistemon citrinus (syn. Callistemon lanceolatus), an Australian species of family Myrtaceae. In India, this small ornamental tree is cultivated in gardens, avenues and road sides and flowers throughout the year. At Agra (Uttar Pradesh, northern India) this species flowers twice a year (February–May and August–November). Flowers open early in the morning and can be characterized as protandrous for a brief period. Fresh open flowers presented ca. 25% of total produced nectar. Nectar sugar composition consisted of only glucose and fructose. A wide array of visitors (honey bees (Apis dorsata), butterflies, wasps, ants, moth, hover flies, several birds and Indian palm squirrel) visit flowers either for pollen or nectar or for facilitating self- and cross-pollination by their intra- and inter-tree movements. Among these, honey bees are dominant in number and in the amount of pollen on their body, while butterflies, ants, wasps, sunbirds, parrots, oriental white-eye sparrow and squirrels forage only for nectar and can be considered occasional pollinators or nectar thieves. Although flowers are highly visited, nectar in standing crop showed that flower visitors did not consume the total nectar produced. Nectar replenishment decreased with age in both bagged- and exposed flowers, showing the capability of secreting nectar after removal during the entire flower lifetime. Experimental hand-pollinations showed that naturalized C. citrinus fruits matured through autogamy, geitonogamy or xenogamy as was reported for native Australian populations. C. citrinus displays an interesting reproductive strategy, shows phenotypic plasticity of flowering periodicity and interacts with a generalized pollinator system, attracts a wide array of animal species with a conspicuous amount or replenished nectar after removals, and uses both compatibility strategies – xenogamy and autogamy – to ensure successful pollination and seed production at native or naturalized habitats.